Enzyme-catalyzed preparation of chenodeoxycholic esters by an immobilized heterologous Rhizopus oryzae lipase - Quintana, Paula G.; Canet, Albert; Marciello, Marzia; Valero, Francisco; Palomo, José Miguel; Baldessari, Alicia (Journal of Molecular Catalysis B: Enzymatic, 2015)
A lipase-catalyzed preparation of ethyl and stearyl esters of chenodeoxycholic acid is described. Stearyl chenodeoxycholate is a new product and both bile acid esters were prepared through an enzymatic approach for the first time. The heterologous Rhizopus oryzae lipase, immobilized on two different supports proved to be an efficient catalyst, even more active than Candida antarctica lipase, in the esterification reaction using a complex substrate such as a bile acid. The immobilization of the enzyme on Octadecyl Sepabeads at pH 7 and 25 °C was the best choice to catalyze the esterification reaction. The influence of various reaction parameters, such as nature of the alcohol, alcohol:substrate ratio, enzyme:substrate ratio, solvent and temperature, was evaluated. Using the response surface methodology and a central composite rotatable design, the conversion of stearyl chenodeoxycholate was optimized by means of the study of the effect of enzyme:substrate ratio and alcohol:substrate ratio. The value 20 for ratios (E/S) and (A/S) was predicted as the optimal value to reach the maximum conversion. However, including economic aspects these ratios can be reduced up to 15. The well-known advantages of biocatalysis and the activity shown by the immobilized heterologous lipase make the reported procedure a convenient way to prepare chenodeoxycholic esters. We thank UBA X010, UBACYT 20020100100304 Universidad de Buenos Aires, PIP 112-200801-00801 Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET) (Argentina) and PICT 2011-00595 Agencia Nacional de Promoción Científica y Tecnológica (Argentina) for partial financial support. We are grateful to Unidad de Microanálisis y Métodos Físicos en Química Orgánica (UMYMFOR) (Consejo Nacional de Investigaciones Científicas y Técnicas-Facultad de Ciencias Exactas y Naturales) for the analytical and spectroscopic determination. AB is a Research Member of CONICET. This work was also supported by the project CTQ2013-42391-R of the Spanish Ministry of Economy and ...